Lysophospholipid receptors signaling and biochemistry - Chun, Jerold, 1959- (Wiley, 2013)
"This state-of-the-art reference addresses lysophospholipids, a special kind of fat that has been found to have a growing number of receptors within the cell and that has important, natural roles in the body, being essential for normal reproduction, development, maturation and life. This book covers the biochemistry, interactions, and signaling of lysophospholipids as well as its potential for producing new therapies for a range of medically important human diseases. Bringing together current knowledge in lysophospholipid signaling, this represents a must-have book for all academic, industrial, and medical school and hospital libraries"--Provided by publisher.